EGR1 Is a Target for Cooperative Interactions between Cholecystokinin and Leptin, and Inhibition by Ghrelin, in Vagal Afferent Neurons - de Lartigue, Guillaume (The Endocrine Society, 2010)
Food intake is regulated by signals from peripheral organs, but the way these are integrated remains uncertain. Cholecystokinin (CCK) from the intestine and leptin from adipocytes interact to inhibit food intake. Our aim was to examine the hypothesis that these interactions occur at the level of vagal afferent neurons via control of the immediate early gene EGR1. We now report that CCK stimulates redistribution to the nucleus of early growth response factor-1 (EGR1) in these neurons in vivo and in culture, and these effects are not dependent on EGR1 synthesis. Leptin stimulates EGR1 expression; leptin alone does not stimulate nuclear translocation, but it strongly potentiates the action of CCK. Ghrelin inhibits CCK-stimulated nuclear translocation of EGR1 and leptin-stimulated EGR1 expression. Expression of the gene encoding the satiety peptide cocaine- and amphetamine-regulated transcript (CARTp) is stimulated by CCK via an EGR1-dependent mechanism, and this is strongly potentiated by leptin. Leptin potentiated inhibition of food intake by endogenous CCK in the rat in conditions reflecting changes in EGR1 activation. The data indicate that by separately regulating EGR1 activation and synthesis, CCK and leptin interact cooperatively to define the capacity for satiety signaling by vagal afferent neurons; manipulation of these interactions may be therapeutically beneficial.